Understanding the characteristics and mechanism of land use transition in mountainous economic zone: A case study of the Chengdu-Chongqing region in southwestern China - Wang, Zhaolin; Ye, Hao; Zhang, Luyang (Frontiers in Environmental Science, 2022)
Abstract: In this paper, land use transfer matrix (LUTM), exploratory spatial data analysis (ESDA), spatial centers of gravity (SCG) and spatial econometric model are used to explore the explicit characteristics and mechanisms of land use transition in mountainous Chengdu-Chongqing region. Our findings indicate that: (1) Characteristics of structural transition of land use in Chengdu-Chongqing region present similarity in two phases. In both phases, the size of cultivated land was in decrease, whilst the size of construction land was in increase, and the increase of construction land was primary from the transfer of cultivated land to construction land. The size of woodland and unused land was in fluctuation, while the size of grassland and water body was in slight decrease. (2) Characteristics of spatial transition of land use in Chengdu-Chongqing region present significant spatial aggregation in different phases. In this period, the gravity center of land use types in the region changed frequently with time. The gravity center of cultivated land moved northwest, the gravity center of woodland moved northeast first and then southwest, the gravity center of grassland moved northeast constantly, the gravity center of water body moved southeast first and then northwest, and the gravity center of unutilized land moved northwest. (3) Land use transition in Chengdu-Chongqing region is driven by many natural and socio-economic factors. The growth of construction land in Chengdu-Chongqing region is significantly impacted by the amount of available resources, economic growth, urbanization rate, population migration and policies. With the expansion of regional economic differences, economic growth and the evolution of industrial structure play crucial roles in the transitions of construction land. The transfers from cultivated land to woodland and grassland are primary affected by the policy for land use and ecological protection. (4) Mechanism of land use transition in Chengdu-Chongqing region shows significant coupling. Land use transition in Chengdu-Chongqing region is a transitional process from conflict to coordination guided by national and regional policies. The conflict in this process is mainly the change of land supply and demand caused by regional economic activities.